Randomised controlled trial of the Limit of Detection of Troponin and ECG Discharge (LoDED) strategy versus usual care in adult patients with chest pain attending the emergency department: study protocol. Issue 10 (2nd October 2018) - Carlton, Edward; Campbell, Sarah; Ingram, Jenny; Kandiyali, Rebecca; Taylor, Hazel; Aziz, Shahid; Beresford, Peter; Kendall, Jason; Reuben, Adam; Smith, Jason; Vickery, Patricia Jane; Benger, Jonathan Richard
Abstract : Introduction: Observational data suggest a single high-sensitivity troponin blood test taken at emergency department (ED) presentation could be used to rule out major adverse cardiac events (MACE) in 10%–60% of ED patients with chest pain. This is done using an 'undetectable' cut-off (the Limit of Detection: LoD). We combined the LoD cut-off with ECG findings to create the LoDED strategy. We aim to establish whether the LoDED strategy works under real-life conditions, when compared with existing strategies, in a way that is cost-effective and acceptable to patients. Methods and analysis: This is a parallel-group pragmatic randomised controlled trial across UK EDs. Adults presenting to ED with suspected cardiac chest pain will be randomised 1:1. Existing rule-out strategies in current use across study centres, using serial high-sensitivity troponin testing, will be compared with the LoDED strategy. The primary outcome is successful early discharge (discharge from hospital within 4 hours of arrival) without MACE occurring within 30 days. Secondary outcomes include initial length of hospital stay; comparative costs; patient satisfaction and acceptability to patients. To detect a 9% difference between the early discharge rates (assuming an 8% rate in the standard care group) with 90% power, 594 patients need to be recruited, assuming a 95% follow-up rate. Ethics and dissemination: The study has been approved by the Frenchay Research Ethics Committee (reference 18/SW/0038). Results will be published in an international peer-reviewed journal. Lay summaries will be made available to patients. Trial registration number: ISRCTN86184521 ; Pre-results.